Intraperitoneal bevacizumab for control of malignant ascites due to advanced-stage gastrointestinal cancers: A multicentre double-blind, placebo-controlled phase II study – AIO SUP-0108. (August 2016) - Jordan, K.; Luetkens, T.; Gog, C.; Killing, B.; Arnold, D.; Hinke, A.; Stahl, M.; Freier, W.; Rüssel, J.; Atanackovic, D.; Hegewisch-Becker, S.
Abstract: Purpose: Malignant ascites is debilitating for patients with advanced cancer. As shown previously, tumour cell production of vascular endothelial growth factor might be a major cause of the formation of malignant ascites. Intraperitoneal bevacizumab could therefore be an option for symptom control in refractory ascites. Patients and methods: Patients with advanced gastrointestinal cancer and malignant ascites who had undergone paracentesis at least twice within the past 4 weeks were randomly assigned in a 2:1 ratio to intraperitoneal bevacizumab (400 mg absolute) or placebo after paracentesis. During the 8-week treatment period, a minimum interval of 14 d was kept between the applications of the study drug. Primary end-point was paracentesis-free survival (ParFS). Results: Fifty-three patients (median age 63 years) were randomised. Forty-nine patients received at least one study drug application and qualified for the main analysis. The proportion of patients with at least one common toxicity criteria grade III–V event was similar with 20/33 (61%) on bevacizumab and 11/16 (69%) on placebo. Median ParFS was 14 d (95% confidence interval [CI]: 11–17) in the bevacizumab arm and 10.5 d (95% CI: 7–21) on placebo (hazard ratio 0.74, 95% CI: 0.40–1.37; P = 0.16). The longest paracentesis-free period was 19 d on bevacizumab (range 6–66 d) and 17.5 d in the placebo arm (range 4–42) ( P = 0.85). Median overall survival was 64 d (95% CI: 45–103) on bevacizumab compared to 31.5 d (95% CI: 20–117) on placebo ( P = 0.31). Conclusion: Intraperitoneal bevacizumab was well tolerated. Overall, treatment did not result in a significantly better symptom control of malignant ascites. However, patients defined by specific immune characteristics may benefit. Highlights: According to pre-clinical data, tumour cell production of VEGF might be a major cause of the formation of malignant ascites. In this randomised phase II study, patients with malignant ascites received intraperitoneal bevacizumab or placebo. Bevacizumab treatment did not result in a significantly better symptom control, nor showed a major influence on survival.